Utilization of the Merdeka Teaching Platform in the Form of Implementing Differentiated Learning - Setiningsih, S; Fitriyah, Qonitah Faizatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This article aims to find out about the utilization of the Merdeka Mengajar platform in differentiated learning. Methodology: The method used in this study is to use a qualitative approach with a phe-nomenological research design. The study was conducted at Sukoharjo 1 Kindergarten with teachers as subjects at the institution. The data collection technique in this study used interviews. Results: The results of this study state that there are 4 stages in implementing the utili-zation of the Merdeka Mengajar platform in the form of implementing dif-ferentiated learning, namely the features in the Merdeka Mengajar Platform that are utilized in differentiated learning, steps in implementing the utiliza-tion of the Merdeka Mengajar platform in the form of implementing differ-entiated learning, obstacles in using the Merdeka Mengajar platform in the form of implementing differentiated learning and teacher strategies in differ-entiated learning using the Merdeka Mengajar Platform. Applications/Originality/Value: 4 stages in implementing the utilization of the Merdeka Mengajar platform